THE PROBLEM OF THE DIGITAL DIVIDE AND WAYS TO OVERCOME IT - Oshanova Н.Т.; Kiynova Ж.Қ.; Kurmankulova Ә.Қ. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
The article discusses the problem of the digital divide and a number of ways to overcome it. Bridging the digital divide is impossible without the development of education. Overcoming illiteracy and training the population in the use of information and communication technologies, computer literacy training are important measures to overcome the digital divide. One of the tools to bridge the digital divide is the development of digital educational resources. The use of digital educational resources in teaching allows you to expand the possibilities of the lesson, as well as increase its effectiveness. It is stated that the teaching materials presented in digital form make it possible to use them without problems at different stages of the lesson and solve the tasks of the lesson. The use of new educational technologies based on modern information and communication technologies can help reduce the digital divide in these countries.